Oxford handbook of the law of the sea - Rothwell, Donald, 1959-; Oude Elferink, Alex G., 1962-; Scott, Karen N. (Karen Nadine), 1975-; Stephens, Tim (Law teacher) (Oxford, United Kingdom : Oxford University Press, 2015)
Human activities have taken place in the world's oceans and seas for most of human history. With such a vast number of ways in which the oceans can be used for trade, exploited for natural resources and fishing, as well as concerns over maritime security, the legal systems regulating the rights and responsibilities of nations in their use of the world's oceans have long been a crucial part of international law. The United Nations Convention on the Law of the Sea comprehensively defined the parameters of the law of the sea in 1982, and since the Convention was concluded it has seen considerable development. This book provides an analysis of its current debates and controversies, both theoretical and practical.--Publisher description.
Historical development of the law of the sea / Tullio Treves -- 1982 United Nations Convention on the Law of the Sea / Robin R. Churchill -- Between stability and change in the Law of the Sea Convention : subsequent practice, treaty modification, and regime interaction / Irina Buga -- Baselines / Coalter G. Lathrop -- Territorial sea and contiguous zone / John E. Noyes -- International straits / Donald R. Rothwell -- Archipelagic regime / Tara Davenport -- Exclusive economic zone / Gemma Andreone -- Continental shelf / Ted L. McDorman -- High seas / Douglas Guilfoyle -- Deep seabed / Michael W. Lodge -- Maritime boundary delimitation / Malcolm D. Evans -- Port and Coastal States / Erik J. Molenaar -- Flag states / Richard A. Barnes -- Landlocked and geographically disadvantaged states / Helmut Tuerk -- United Nations : a practitioners perspective / Hans Corell -- Law of the Sea Convention institutions / James Harrison -- Courts and tribunals : The ICJ, ITLOS, and arbitral tribunals / Bernard H. Oxman -- International Maritime Organization / Aldo Chircop -- Regional fisheries management organizations / Rosemary Rayfuse -- Integrated oceans management : a new frontier in marine environmental protection / Karen N. Scott -- Marine living resources / t
"Table of cases": pages xiii-xviii.
"Table of treaties": pages xix-xlv.
Includes bibliographical references and index.
Keywords: Law of the sea; Maritime law; Droit de la mer; Droit maritime; Recherche marine; 2; Ressources de la mer; 2; Droit international; Law of the sea; Maritime law; 2; 2